The complete mitochondrial genome of Rhodeus lighti (Cypriniformes: Cyprinidae): sequencing and analysis. (3rd May 2016) - Li, Chun-Hong; Jin, Shu-Gang; Dong, Yu-Long; Wang, Li; Shi, Wan-Yu
Abstract: Phylogenetic placement of Rhodeus lighti ( R. lighti ) remains unresolved. We determined the first complete mitochondrial genome of R. lighti (Cypriniformes: Cyprinidae). The genome is 16, 597 bp in length. It consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 2 non-coding regions. The gene composition and order were similar to most of the other vertebrates. The complete mitochondrial genome sequence of R. lighti should contribute towards clarifying the systematics of Rhodeus fishes. The phylogenetic relationships using partitioned Neighbor-Joining tree indicated that (((((Pseudorasbora, Rhodeus) Ctenopharyngodon) (Acheilognathus, Tanakia) Carassius)) Danio rerio). This study will contribute to confirm the phylogenetic status of Rhodeus within family Cyprinidae.